EFFICACY OF AYURVEDIC TREATMENT IN VICHARCHIKA WITH SPECIAL REFERNCE TO JALUKAVACHARANA- A CASE STUDY - P. Roshni K. (International Journal of Applied Ayurved Research, 2017)
Skin is the first organ of the body interacting with the environmental agents like physical, chemical and biological agents. Variations in the environmental stimuli and natural ability of body to deal with these factors result in spontaneous remissions and relapses. Skin is a mirror that reflects internal and external pathology and thus helps in diagnosis of diseases. Skin complaints affects all ages from the neonates to the elderly and cause harm in a number of ways, such as discomfort, disfigurement and disability. All the skin diseases in Ayurveda have been described under the heading of ‘Kustha’, which are further divided into Maha Kustha and Kshudra Kustha. Vicharchika one of the Kshudra Kustha runs a chronic course generally considered difficult to cure and even if it is cured relapses are common; Vicharchika has been simulated with the diseases ‘Eczema’ or Dermatitis by most of the scholars.Rakta Dusti as one of the prime causes of skin diseases; on the other hand, patients may get relief after letting out the vitiated blood. Sushruta provides useful guidelines for bloodletting and claims it as most valuable therapy in half of all ailments. Among various methods for bloodletting, Jalaukavacharana karma by Jalauka (Leech) is considered as the ideal method to expel out the vitiated blood safely, quickly and effectively.This single case study points out the efficacy of ayurvedic treatment modalities in vicharchika with special reference to jalukavacharana.